Investigating long-term retest effects in the GHQ-12 - David J. Pevalin (University of Essex, Institute for Social and Economic Research (ISER), 2000)
The aim of this analysis was to examine data from a general population sample for any retest effects in the 12-item General Health Questionnaire. A core panel was drawn from the British Household Panel Survey (n=4749) of those who had completed the GHQ-12 seven times from 1991 to 1997. The panel results were compared with cross-sectional data from the Health Surveys for England for the same years. No evidence of retest effects was found. The age composition of the panel and the distribution of GHQ scores with age are discussed in light of these findings.
Keywords: 330